2015
DOI: 10.3109/01676830.2015.1049372
|View full text |Cite
|
Sign up to set email alerts
|

Giant Blue Nevus: A New Association to Nevus of Ota

Abstract: Nevus of Ota, also known as oculodermal melanocytosis, is a congenital pigmentary condition that can affect structures in the distribution of the ophthalmic and maxillary divisions of the trigeminal cranial nerve. Malignant transformation, although rare, may occur within nevus of Ota and result in uveal, cutaneous, orbital or even dural melanoma. We present a new association of Nevus of Ota complicated with a giant orbital Blue Nevus in a young white male and the management of this tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
(7 reference statements)
0
3
0
4
Order By: Relevance
“…In 1973, Speakman and Phillips [13] reported two cases of cellular and malignant blue nevus presenting in the orbit in patients with oculodermal melanosis. Similarly, in 2015, Medel et al [14] reported a third case of giant orbital cellular blue nevus and oculodermal melanocytosis in a 20-year-old male that was managed with excisional biopsy. Buntinx-Krieg et al [15] went on to report a 45-year-old female with oculodermal melanocytosis and orbital cellular blue nevus that subsequently underwent transformation to malignant melanoma.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In 1973, Speakman and Phillips [13] reported two cases of cellular and malignant blue nevus presenting in the orbit in patients with oculodermal melanosis. Similarly, in 2015, Medel et al [14] reported a third case of giant orbital cellular blue nevus and oculodermal melanocytosis in a 20-year-old male that was managed with excisional biopsy. Buntinx-Krieg et al [15] went on to report a 45-year-old female with oculodermal melanocytosis and orbital cellular blue nevus that subsequently underwent transformation to malignant melanoma.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Em relato mostrado por Medel et al (2015) um homem, branco, jovem de 20 anos apresentou-se para consulta com queixa de proptose indolor do olho direito, observado algumas semanas antes. Ele havia sido diagnosticado com nevo de Ota no olho direito aos 5 anos de idade e confirmado com uma biópsia aos 10 anos em outra instituição.…”
Section: Discussionunclassified
“…Uma Punção Aspirativa por Agulha Fina (PAAF) foi realizada e relatou nevo azul atípico, mas era impossível descartar o melanoma maligno com a amostra. Dado o comportamento clínico da massa, o tempo de evolução e a dificuldade de estabelecer um diagnóstico histológico claro com a PAAF, a cirurgia não conservadora foi proposta (MEDEL et al, 2015).…”
Section: Discussionunclassified
“…Contrastingly, cellular blue nevi, commonly found on the buttocks or scalp, are a typically benign variant of common blue nevi that are histologically characterized by dense cellularity and abundant melanin. The term “atypical cellular blue nevus” (ACBN) is used to describe borderline forms of cellular blue nevus with additional features (asymmetry, hypercellular foci, focal cytologic atypia, and occasional mitoses) that are suggestive of melanoma but not definitive [ 4 ]. There are few case reports describing the malignant potential of these histologically distinct lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenomena showing the malignant potential of nevus of Ota and cellular blue nevus have been reported. Medel, et al described a Caucasian man with a nevus of Ota and ocular melanosis at the inferior fornix of the right eye that appeared to extend into the orbital space [ 4 ]. This patient had worsening proptosis, and a post-excisional diagnosis of atypical giant cellular blue nevus on a nevus of Ota was made.…”
Section: Discussionmentioning
confidence: 99%